How to do a robotic lateral pelvic side wall dissection for rectal cancer. Issue 3 (14th January 2022) - Jiang, William; Lokuhetty, Naradha; Mohan, Helen M.; Larach, José Tomás; Waters, Peadar; Heriot, Alexander G.; Warrier, Satish K.
Abstract : Our article describes the anatomy, technical steps, common pitfalls, and our recommendations for performing a successful robotic lateral pelvic side wall dissection for rectal cancer. This is supplemented with videos and an image to clearly demonstrate our technique.